1979
DOI: 10.1002/cber.19791121206
|View full text |Cite
|
Sign up to set email alerts
|

Eine umkehrbare Gerüstumlagerung im trans‐Erythrinan‐Ringsystem, III. Abbau des 1(6→7) abeo‐trans‐Erythrinan‐Gerüstes

Abstract: Durch Fragmentierung des Acetat-mesylats 4 mit Natriummethylat entsteht der 0-Lactamaldehyd 9, der sich uber die Carbonsaure 21 zum 0-Lactam 22 abbauen 1 a t . Die Konstitution von 9 wird mit Hilfe deuterierter Verbindungen ermittelt und durch eine Rontgenstrukturanalyse bewiesen. Folgeprodukte des Abbaus sind die Spirodienone 24 und 25 mit C-und B-Nor-erythrinan-Gertist. Durch Reduktion von 22 zu 26 und Cyclodehydratisierung wird die B-Nor-cis-erythrinan-Base 30 gewonnen. A Reversible Rearrangement of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The corresponding eis-diol formed a monoacetate without any rearrangement. Further studies [177] revealed that fragmentation of the acetate-mesylate (161b) with sodium methoxide led to the /?-lactam aldehyde (162a), which was degraded to the /Mactam (162b) via the carboxylic acid. Further studies [177] revealed that fragmentation of the acetate-mesylate (161b) with sodium methoxide led to the /?-lactam aldehyde (162a), which was degraded to the /Mactam (162b) via the carboxylic acid.…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%
“…The corresponding eis-diol formed a monoacetate without any rearrangement. Further studies [177] revealed that fragmentation of the acetate-mesylate (161b) with sodium methoxide led to the /?-lactam aldehyde (162a), which was degraded to the /Mactam (162b) via the carboxylic acid. Further studies [177] revealed that fragmentation of the acetate-mesylate (161b) with sodium methoxide led to the /?-lactam aldehyde (162a), which was degraded to the /Mactam (162b) via the carboxylic acid.…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%